2019
DOI: 10.1155/2019/5198138
|View full text |Cite
|
Sign up to set email alerts
|

Keap1 Cystenine 151 as a Potential Target for Artemisitene-Induced Nrf2 Activation

Abstract: Artemisitene (ATT) activates the nuclear factor (erythroid-derived 2)-like 2 (Nrf2) by increasing its stabilization and reducing ubiquitination. The cysteine (Cys) residues of the cytosolic Nrf2 repressor Kelch-like ECH-associated protein-1 (Keap1) function as redox sensors and may be crucial in activating Nrf2. To determine whether ATT-induced Nrf2 activation is dependent on the modification of Keap1 and to elucidate the underlying mechanism, we transfected cell lines with six different Keap1 mutant construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In addition, Chen et al revealed that ATT serves as a novel nuclear factor erythroid 2-related factor 2 (Nrf2) activator that could induce an antioxidant response in an Nrf2-dependent manner by alleviating Nrf2 ubiquitination and increasing its stability and suppress lung injury induced by bleomycin ( Chen et al, 2016 ). Subsequently, Liu et al reported that the cysteine (Cys) residues of the cytosolic Nrf2 repressor Kelch-like ECH-associated protein-1(Keap1) might be a potential target contributing to ATT-stimulated Nrf2 activation and is indispensable for stabilizing Nrf2 and facilitating Nrf2-mediated transcription of downstream genes ( Liu et al, 2019 ). Recently, researchers found that ATT could block the production of reactive oxygen species (ROS, especially mitochondrial ROS) and prevent NLRP3 inflammasome assembly and activation, resulting in the decrease of IL-1β production ( Hua et al, 2022 ).…”
Section: Biological Activities Of Attmentioning
confidence: 99%
“…In addition, Chen et al revealed that ATT serves as a novel nuclear factor erythroid 2-related factor 2 (Nrf2) activator that could induce an antioxidant response in an Nrf2-dependent manner by alleviating Nrf2 ubiquitination and increasing its stability and suppress lung injury induced by bleomycin ( Chen et al, 2016 ). Subsequently, Liu et al reported that the cysteine (Cys) residues of the cytosolic Nrf2 repressor Kelch-like ECH-associated protein-1(Keap1) might be a potential target contributing to ATT-stimulated Nrf2 activation and is indispensable for stabilizing Nrf2 and facilitating Nrf2-mediated transcription of downstream genes ( Liu et al, 2019 ). Recently, researchers found that ATT could block the production of reactive oxygen species (ROS, especially mitochondrial ROS) and prevent NLRP3 inflammasome assembly and activation, resulting in the decrease of IL-1β production ( Hua et al, 2022 ).…”
Section: Biological Activities Of Attmentioning
confidence: 99%
“…Activation of the Nrf2-ARE signaling contributed to the ferroptotic resistance in cisplatin-resistant HNC cells [ 45 ]. Liu et al discovered that ART covalently targets Keap1 at Cys151 to activate the Nrf2-dependent pathway [ 94 , 95 ]. Inhibition of Nrf2 production can reduce resistance to ART in cisplatin-resistant HNCs [ 46 ].…”
Section: Mechanisms Of Art-induced Ferroptosismentioning
confidence: 99%
“…Among them, Cys273 and Cys288, both of which reside in the region of the IVR domain, are critical for Keap1 to inhibit Nrf2 under normal conditions, whereas a subset of Nrf2 activators target Cys151 which locate in the BTB domain [ 55 , 56 ]. Recent findings have shown that the modification of Cys151 residue in Keap1 is crucial in activating Nrf2 by artemisitene and curcumin [ 56 , 57 ] ( Figure 2 ). Apart from the canonical mechanism to activate Nrf2 by oxidising Keap1 cysteine, other noncanonical Nrf2 regulatory pathways have been found under stressful conditions.…”
Section: Antioxidative Stress-related Pathways That Lead To Therapmentioning
confidence: 99%